Public perception of halal medicine certification - Utami, Zhazha Zetira; Nurkhasanah, Nurkhasanah (Universitas Ahmad Dahlan, 2021)
The trend of the halal industry has increased, both in the world and in Indonesia. The development of halal industry trend has developed in all fields, one of which is halal certification of drugs. Drug products are now also a special concern in the halal product category because, in terms of treatment, society demands that the health products used must be of high quality and halal. The purpose of the study was to find out how the public's perception of halal drug certification and whether there was a relationship between the level of knowledge and the perception of drug halal certification. This type of research is an analytic observational research survey section with a cross-sectional approach. Obtained 102 respondents, then the data were analyzed using the SPSS application, both univariate and bivariate analysis. The results showed that the level of knowledge was moderate (63.7%), the level of perception was good (64.7%) and the level of behavior was good (64.7%). Knowledge has a linear relationship (sig value 0.168 > 0.05) significantly (f value 1.557 < 2.20) to respondents' perceptions of halal certification of drugs, and perceptions of drug halal certification also have a linear relationship (sig value 0.119 > 0, 05) significantly (f value 1.805 < 2.31) on the respondent's drug consumption behavior. Public perception of drug halal certification is good (64.7%) and the better the level of knowledge, the better the perception of drug halal certification (significantly linear).